Submission inspection checklist for concreting, structural steel and other major works of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding submission inspection checklist for concreting, structural steel and other major works of BRAC University new campus project.